2009
DOI: 10.1007/s10534-009-9271-y
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure, DNA binding studies, nucleolytic property and topoisomerase I inhibition of zinc complex with 1,10-phenanthroline and 3-methyl-picolinic acid

Abstract: Crystal structure analysis of the zinc complex establishes it as a distorted octahedral complex, bis(3-methylpicolinato-kappa(2) N,O)(2)(1,10-phenanthroline-kappa(2) N,N)-zinc(II) pentahydrate, [Zn(3-Me-pic)(2)(phen)]x5H(2)O. The trans-configuration of carbonyl oxygen atoms of the carboxylate moieties and orientation of the two planar picolinate ligands above and before the phen ligand plane seems to confer DNA sequence recognition to the complex. It cannot cleave DNA under hydrolytic condition but can slightl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…Circular dichroic spectral technique is useful in diagnosing changes in DNA morphology during drug–DNA interactions. The CD spectrum of the B‐form of double‐stranded CT‐DNA is mainly attributed to the presence of two characteristic peaks: 245 nm (negative) due to right‐handed helicity; and 275 nm (positive) due to nucleobase stacking that are quite sensitive to the mode of DNA interactions with small molecules . For a number of DNA‐binding molecules, several binding modes are known to occur in parallel.…”
Section: Resultsmentioning
confidence: 99%
“…Circular dichroic spectral technique is useful in diagnosing changes in DNA morphology during drug–DNA interactions. The CD spectrum of the B‐form of double‐stranded CT‐DNA is mainly attributed to the presence of two characteristic peaks: 245 nm (negative) due to right‐handed helicity; and 275 nm (positive) due to nucleobase stacking that are quite sensitive to the mode of DNA interactions with small molecules . For a number of DNA‐binding molecules, several binding modes are known to occur in parallel.…”
Section: Resultsmentioning
confidence: 99%
“…These assays were carried out as described previously [28]. The apparent binding constants of the [Co(phen)(ma)Cl] and [Co(ma) 2 (phen)] complexes (ma = maltolate) for the various DNA duplexes and G-quadruplex are tabulated in Table 5. 2.9.…”
Section: Ethidium Bromide(eb) and Thiazole Orange Quenching Assays Anmentioning
confidence: 99%
“…Ethidium bromide and thiazole orange quenching assays have been successfully used to determine the DNA binding affinity and sequence selectivity of small organic molecules and metal complexes [28,[46][47][48][49][50]. A compound with a higher binding constant for a given DNA determined by either assay is said to have a higher binding affinity.…”
Section: Dna Binding Studies and Restriction Enzyme Inhibitionmentioning
confidence: 99%
“…It is an important nuclear enzyme in cellular process that can control the topological state of DNA . Many studies have shown that a variety of antitumor drugs have been found to inhibit DNA topoisomerase . For example, camptothecin and its derivatives are known to be the inhibitors of DNA Topo I and show excellent antitumor activity against a broad spectrum of tumor .…”
Section: Introductionmentioning
confidence: 99%
“…For example, camptothecin and its derivatives are known to be the inhibitors of DNA Topo I and show excellent antitumor activity against a broad spectrum of tumor . Recently, some ruthenium complexes have been reported to inhibit topo I activity . For example, Chao et al .…”
Section: Introductionmentioning
confidence: 99%